2017
DOI: 10.1002/2017wr021644
|View full text |Cite
|
Sign up to set email alerts
|

A Pseudo‐Vertical Equilibrium Model for Slow Gravity Drainage Dynamics

Abstract: Vertical equilibrium (VE) models are computationally efficient and have been widely used for modeling fluid migration in the subsurface. However, they rely on the assumption of instant gravity segregation of the two fluid phases which may not be valid especially for systems that have very slow drainage at low wetting phase saturations. In these cases, the time scale for the wetting phase to reach vertical equilibrium can be several orders of magnitude larger than the time scale of interest, rendering conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Conventionally, the field-scale impact of capillary pressure has been evaluated without consideration of small-scale heterogeneities. In homogeneous reservoirs capillarity leads to an increase in the sweep of the plume and retardation of its lateral migration (Golding et al, 2013;Becker et al, 2017). We have shown that the presence of structured heterogeneities can lead to an outcome which has qualitatively the opposite impact.…”
Section: Field-scale Implications and Discussionmentioning
confidence: 84%
“…Conventionally, the field-scale impact of capillary pressure has been evaluated without consideration of small-scale heterogeneities. In homogeneous reservoirs capillarity leads to an increase in the sweep of the plume and retardation of its lateral migration (Golding et al, 2013;Becker et al, 2017). We have shown that the presence of structured heterogeneities can lead to an outcome which has qualitatively the opposite impact.…”
Section: Field-scale Implications and Discussionmentioning
confidence: 84%
“…Vertical drainage in this state continues only at a very low rate and is not reproduced by the VE model, which assumes that no brine phase above residual saturation is held back in the gas plume. This could be improved by a pseudo‐VE model that assumes a pseudo‐residual brine phase saturation in the plume, which is higher than the residual saturation and reduced dynamically due to slow vertical drainage (Becker et al, ). We note that the full multidimensional model does not necessarily give better solutions in the VE subdomain.…”
Section: Resultsmentioning
confidence: 99%
“…Conventionally, the field‐scale impact of capillary pressure has been evaluated without consideration of small‐scale heterogeneities. In homogeneous reservoirs capillarity leads to an increase in the sweep of the plume and retardation of its lateral migration (Becker et al, 2017; Golding et al, 2013). We have shown that the presence of structured heterogeneities can lead to an outcome which has qualitatively the opposite impact.…”
Section: Field‐scale Implications and Discussionmentioning
confidence: 99%
“…Conventionally, the field-scale impact of capillary pressure has been evaluated without consideration of small-scale heterogeneities. In homogeneous reservoirs capillarity leads to an increase in the sweep of the plume and retardation of its lateral migration (Becker et al, 2017;Golding et al, 2013). We have shown that the presence of structured heterogeneities can lead to an outcome which has qualitatively the opposite R 1 is the central vertical distance from the top of the plume to the caprock (initially ≈40 m from the top of the injection well to the caprock), and R 2 is the growing lateral extent of the plume directly under the caprock for x > 1,000 m, once the plume has reached the caprock.…”
Section: Field-scale Implications and Discussionmentioning
confidence: 99%